Camparision Results of Administration of Glucoseamine and Glucoseamine with Alendronate in Symptomatic Relieve of Knee DJD - Hamid Reza Arti; Seyed Abdolhossin Mehdinasab; Naser Sarafan (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Degenerative Joint disease(DJD) is the most common joint disease in human and the most cause of chronic disability in aging papulation in developed countries. Several studies explain that glocosamine Is better than plasebo and its efficacy is more in comparison with NSAID in knee osteoarthritic patient.Alendronate is prescribed for osteoprothic patients. The aim of this study was to compare the efficacy of adminstration of glocoseamine alone and in combination with alendronate in osteoarthritis of the knee.Subjects and Methods: A total of 130 patients of either sex with osteoarthritis were included in the study and randomised to receive glocoseamine alone (500mg TDS) and combination of Glocoseamine (500mg TDS) and alendronate (70mg weeky) for 12weeks. The patients were evaluated at 1;3;6 and 12weeks for efficacy.Results: There was not statisticaly significant decrease in pain index (p>0.05) but in total therapy the mean of pain is decreased.The stiffnes index in combination therapy was decreased (p<0.05).The function of joint in combination therapy was improved after 12 weeks. The BMD after 12 weeks combination therapy was improved.Conclusion: Combination therapy of glocoseamine and alendronate was significant improvement of stiffness, function, BMD of osteoarthritis compared with glocoseamine alone but there was not statistically significant decreased in pain index. It can be concluded that the combination of glocoseamine with alendronate provide better and more rapid improvement in patients with osteoarthritis.